Oxidative Stress and Lipid Peroxidation: Prospective Associations Between Ferroptosis and Delayed Wound Healing in Diabetic Ulcers - Feng, Jiawei; Wang, Jialin; Wang, Yuqing; Huang, Xiaoting; Shao, Tengteng; Deng, Xiaofei; Cao, Yemin; Zhou, Mingmei; Zhao, Cheng (Frontiers in Cell and Developmental Biology, 2022)
Diabetic ulcers are one of the major complications of diabetes, and patients usually suffer from amputation and death due to delayed ulcer wound healing. Persistent inflammation and oxidative stress at the wound site are the main manifestations of delayed wound healing in diabetic ulcers. In addition, chronic hyperglycemia in patients can lead to circulatory accumulation of lipid peroxidation products and impaired iron metabolism pathways leading to the presence of multiple free irons in plasma. Ferroptosis, a newly discovered form of cell death, is characterized by intracellular iron overload and accumulation of iron-dependent lipid peroxides. These indicate that ferroptosis is one of the potential mechanisms of delayed wound healing in diabetic ulcers and will hopefully be a novel therapeutic target for delayed wound healing in diabetic patients. This review explored the pathogenesis of diabetic ulcer wound healing, reveals that oxidative stress and lipid peroxidation are common pathological mechanisms of ferroptosis and delayed wound healing in diabetic ulcers. Based on strong evidence, it is speculated that ferroptosis and diabetic ulcers are closely related, and have value of in-depth research. We attempted to clarify prospective associations between ferroptosis and diabetic ulcers in terms of GPX4, iron overload, ferroptosis inhibitors, AGEs, and HO-1, to provide new ideas for exploring the clinical treatment of diabetic ulcers.